Proyecto de formación edafológica para la I.E.T.A Fernández Guerra de Santander de Quilichao - Cauca (2020)
The work´s topic was to formulate a proposal for edaphological training for the I.E.T.A Fernández Guerra of Santander de Quilichao, Cauca, through the pedagogical model “significant learning”. Because, the institution is technical character, it require a structuring of the programmatic contents based on the General Education Law 115 of 2004, the curricular guidelines and the basic competence standards of the Ministry of National Education, which respond to the needs of learning and job performance of its students, through fundamentals and theoretical-practical tools for the development of the soil component: characterization, management and conservation. Thus, this proposal will be a reference to move forward with the structuring of the other water and air components of the institution. Keywords: